Fireflies in Art: Emphasis on Japanese Woodblock Prints from the Edo, Meiji, and Taishō Periods - Deirdre A. Prischmann-Voldseth (Insects, 2022)
Examining how insects are represented in artwork can provide insight into people’s perceptions and attitudes towards arthropods, as well as document human–insect interactions and how they change through time. Fireflies are well-known bioluminescent beetles (Coleoptera: Lampyridae) of great cultural significance, especially in Japan. A selection of online museum collections, art databases, and dealer websites were used to find artwork featuring fireflies, with an emphasis on Japanese ukiyo-e wood block prints from the Edo, Meiji, and Taishō time periods (1600–1926). Quotes from early twentieth century texts were used to provide additional historical context. Over 90 different artists created artwork featuring fireflies, including several renowned masters. Artists depicted adult fireflies in a variety of ways (e.g., relatively accurately, more generalized, symbolic or abstract, yellowish dots) in the absence and presence of people. Most images were set outdoors during the evening near water, and primarily featured women and children, groups of women, and large parties catching fireflies or observing caged fireflies. ‘Beauties’, geisha, courtesans, kabuki actors, and insect vendors were also common subjects. Various types of collecting tools and a diversity of cages were featured, as well as insect vendors. The artwork highlights the complex connections between fireflies and humans. Insect-related art can contribute to education and conservation efforts, particularly for dynamic insects such as fireflies that are facing global population declines.